2021
DOI: 10.1126/sciimmunol.abl9105
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection generates tissue-localized immunological memory in humans

Abstract: Adaptive immune responses to SARS-CoV-2 infection have been extensively characterized in blood; however, most functions of protective immunity must be accomplished in tissues. Here, we report from examination of SARS-CoV-2 seropositive organ donors (ages 10 -74) that CD4 + T, CD8 + T, and B cell memory generated in response to infection is present in bone marrow, spleen, lung, and multiple lymph nodes (LNs) for up to 6 months post-infection. Lungs and lung-associated LNs were the most prevalent sites for SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(201 citation statements)
references
References 68 publications
11
186
2
2
Order By: Relevance
“…The presence of long-lived plasma cells in the bone marrow of SARS-CoV-2-infected individuals further supports this model, as high-affinity plasma cells are predominantly derived from GCs 42 , 64 . Indeed, a robust GC and T FH cell response that persists for up to 6 months has been identified in humans and rhesus macaques following SARS-CoV-2 infection 65 , 66 .…”
Section: B Cell Response To Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of long-lived plasma cells in the bone marrow of SARS-CoV-2-infected individuals further supports this model, as high-affinity plasma cells are predominantly derived from GCs 42 , 64 . Indeed, a robust GC and T FH cell response that persists for up to 6 months has been identified in humans and rhesus macaques following SARS-CoV-2 infection 65 , 66 .…”
Section: B Cell Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…B cells are found in many mucosal tissues in humans 154 . SARS-CoV-2 infection induces virus-specific memory B cells in the bone marrow, spleen, lungs and lymph nodes 66 . Residual antigen depots are also present in mucosal tissues, including in the gut, following SARS-CoV-2 infection, and may fuel the continued clonal evolution of B cells in these sites 40 , 63 , 155 .…”
Section: Approaches To Induce a Broadly Reactive Memory B Cell Responsementioning
confidence: 99%
“…However, blood contains a small fraction of the total immune cells throughout the body and lacks tissue-resident immune cells , including TRM (Farber, 2021;Poon and Farber, 2020;Weisberg et al, 2021b). The generation of memory T cell responses to infection and vaccination can be followed in peripheral blood (Akondy et al, 2017;Dan et al, 2021;Graham et al, 2020;Hammarlund et al, 2003;Thom et al, 2021), though studies of infection or vaccination sites have revealed distinct dynamics, functions, and immune cell compositions compared with blood (Guvenel et al, 2020;Patel et al, 2018;Szabo et al, 2021;Poon et al, 2021). Defining the full heterogeneity of virus-specific T cell responses therefore requires comprehensive profiling across multiple sites.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we also observed the activation and secretion of antiviral cytokines and chemokines in lung tissue from vaccinated mice and correlated their production with rapid protection in hamsters. (ii) We believe that robust and local RBD-specific T cell responses should contribute to providing effective protection against SARS-CoV-2 infection 37 . Considering resident memory CD8 + T cells, which are thought to provide long-lasting and broad-spectrum immune protection for LAIVs 38 , our data suggest that dNS1-RBD has the potential to confer long-lasting protective immunity, particularly around the bronchoalveolar space and lungs.…”
Section: Discussionmentioning
confidence: 99%